PENGGUNAAN DIKSI DALAM TEKS BERITA SISWA KELAS XI SMA NEGERI 1 SUNGAI TARAB - Rieska Dinda Savitri; Emidar (EDU RESEARCH, 2024)
This research aims to analyze the use of diction in news texts written by class XI students of SMA Negeri 1 Sungai Tarab. Diction is an important aspect in news texts because it determines the clarity, accuracy and effectiveness of the information conveyed. This research uses a qualitative method with a descriptive approach. Data was obtained from 22 news texts consisting of 63 paragraphs and 2,196 words. The research results show that in general students have been able to choose the right diction in writing news texts, with 1,821 words categorized as appropriate, 1,738 words accurate, and 1,380 words appropriate to the context of their use. However, errors were still found in word selection, where there were 375 inappropriate words, 458 inaccurate words, and 816 inappropriate words in the text analyzed.